2021
DOI: 10.1016/j.bjoms.2020.08.099
|View full text |Cite
|
Sign up to set email alerts
|

Oral and maxillofacial surgery patient satisfaction with telephone consultations during the COVID-19 pandemic

Abstract: Introduction Due to the COVID-19 pandemic most Oral and Maxillofacial Surgery (OMFS) units have moved to conducting patient consultations over the telephone. The aim of this study was to assess patient satisfaction with telephone consultations during the COVID-19 pandemic. Methods A retrospective survey was conducted of OMFS patients at our hospital who had telephone consultations between 1 st April-8 th June 2020. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Among the patients who participated in the telepsychiatry service, the majority (94.3%) were satisfied with the quality of the healthcare they received. The patients' satisfaction was in line with the existing literature that found patients' satisfaction with the care quality and clinical outcomes following telehealth visits superior to those of traditional medical setting visits [18][19][20]. Our study did not find any differences in satisfaction levels with respect to patients' demographic characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…Among the patients who participated in the telepsychiatry service, the majority (94.3%) were satisfied with the quality of the healthcare they received. The patients' satisfaction was in line with the existing literature that found patients' satisfaction with the care quality and clinical outcomes following telehealth visits superior to those of traditional medical setting visits [18][19][20]. Our study did not find any differences in satisfaction levels with respect to patients' demographic characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…Even prior to the COVID-19 pandemic, 30% of all GP consultations are via telephone, video or online [ 22 ]. Since the pandemic, this has shifted to about 70%, and other surgical specialties, including orthopaedics [ 23 ] and maxillofacial surgery [ 24 ], have also begun utilising remote consultations. This study adds to the increasing evidence base that patients are satisfied with such a modality of clinical consult.…”
Section: Discussionmentioning
confidence: 99%
“…Other surgical specialties have reported much higher rates of patient satisfaction with the implementation of remote consultations during a similar time period, to the extent that 83% of patients attending a British general maxillofacial clinic [ 24 ] and 93% from a larger group of American orthopaedics clinic patients [ 27 ] would be willing to attend a similar remote consultation again. Our modest number of 55% may in part reflect the unique challenges of delivering a 2WW cancer triage service over the phone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies investigated patient satisfaction with video/phone consultations during the COVID-19 pandemic, both in allergy/immunology and other services (e.g. rheumatology, inflammatory bowel disease, oral/maxillofacial surgery, urology), and all confirmed high satisfaction levels in the majority of patients [14][15][16][17][18][19][20]. In addition, some other studies, mainly involving allergy/immunology clinics, reported increased prescriptions of home-administered biologics [21][22][23].…”
Section: Discussionmentioning
confidence: 85%